1980
DOI: 10.1104/pp.66.3.395
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Aliphatic Alcohols on Leaf Senescence

Abstract: Because of the effects of ethanol used as a solvent in other experiments, the action of aliphatic alcohols on leaf senescence in the dark has been studied systematically. These compounds both maintain chlorophyll and prevent proteolysis in the dark, much as do the cytokinins and other senescence-delaying substances. The activity of the straight-chain alcohols increases in a log-linear fashion with increasing chain length up to 1-octanol. Introduction of a branch in the chain or of a second OH group greatly dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…If cytokinin action in the mitochondria is important to plant growth and development, one might anticipate that some of these compounds could produce 'cytokinin' effects. In this regard, it is interesting that certain alcohols delay leaf senescence and so do cytokinins (10). However, we failed to observe stimulation of cell division in soybean tissue cultures when we tested a number of the compounds (to be reported elsewhere).…”
Section: Discussionmentioning
confidence: 73%
“…If cytokinin action in the mitochondria is important to plant growth and development, one might anticipate that some of these compounds could produce 'cytokinin' effects. In this regard, it is interesting that certain alcohols delay leaf senescence and so do cytokinins (10). However, we failed to observe stimulation of cell division in soybean tissue cultures when we tested a number of the compounds (to be reported elsewhere).…”
Section: Discussionmentioning
confidence: 73%
“…Visibly, they turn yellow or lose their color. This is a consequence of the deg- radation of chlorophyll and proteins and can be retarded, to some extent, if the excised leaves are treated with cytokinins (Richmond and Lang 1957), or substances with anti senescence effects (Satler and Thimann 1980, Thomas and Katterman 1986, Cavender et al 1988. Significantly cytokinin-like activity manifested solely by derivate No.…”
Section: Discussionmentioning
confidence: 99%
“…The gradual overall respiratory rise parallels the slow Chl disap- In tissues whose respiratory systems are insensitive to cyanide, it is commonly found that they are sensitive to hydroxamic acids such as SHAM or CLAM (18). For our purpose, SHAM was unsuitable as an inhibitor because its low water solubility requires the use of alcoholic solutions, which themselves exert powerful effects on senescence (16). Potassium benzyl hydroxamate, BAM, is water-soluble up to above 100 mm and was therefore adopted.…”
Section: Methodsmentioning
confidence: 99%